Optimized Microwave-Assisted Blanching of Fresh Tomatoes (Solanum lycopersicum L.) - Andi Eko Wiyono; Miftahul Choiron; Sigit Arya Putra; Muhammad Luthfi Nashiruddin (Jurnal Ilmu Pertanian Indonesia, 2026)
Research was conducted to discover the ideal microwave blanching parameters for producing high-quality tomatoes. The experiment employed response surface methodology (RSM) with Box Behnken Design (BBD) and consisted of 17 treatments; each treatment combination was tested in duplicate. The independent variables were power (W) (X1), time (sec) (X2), and blanching water (mL) (X3). The experimental results were analyzed using ANOVA, and the optimization process was carried out and verified. The best treatment outcomes were obtained using a combination of 200 W power, 120 sec duration, and 450 mL of blanching water. After validation, the optimal yield response was 100.01%, with total soluble solids at 3.6 ºBrix, vitamin C at 154 mg/100 g, and total tomato carotene at 3.3 mg/100 g. Overall, these data have a 95% confidence interval ranging from low to high.Keywords: blanching, microwave-assisted, optimization, response surface methodology, tomatoes